Biblical themes in science fiction - Tilford, Nicole L.; Murphy, Kelly J., 1979- (Bible and its reception, 2023)
'Biblical Themes in Science Fiction' is a handbook for exploring how biblical themes appear in contemporary science fiction. Contributors examine the relationship between ancient and modern depictions of Adam and Eve, the tower of Babel, Noah's ark, handmaids, utopian cities, the promised land, the city of Babylon, messiahs, resurrection, and the apocalypse. Essays are supplemented by images and key science fiction sources for diving deeper into how the Bible influenced authors of not only literature but of films and video games as well. An afterword considers the imaginative impulses common to both science fiction and biblical texts.